RANCANG BANGUN SISTEM INFORMASI PERENCANAAN KEBUTUHAN BAHAN BAKU MENGGUNAKAN METODE LOT FOR LOT PADA PT. ELANG JAGAD - Fatkurrotin, Shofia; Setiawan, Henry Bambang; Maulana, Yoppy Mirza (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2015)
PT. Elang Jagad is a company applying strategy Make-to-Order in inventories of raw material. PT. Elang Jagad often have inaccuracies in fulfilling orders from it’s customers according to the number and order fulfillment time that has been set (due date). So PT. Elang Jagad experiencing problems calculating material requirements planning such as, customer order fulfillment are often experiencing delays, which will result in lost customers (stock out).Through the analysis of data in 2011 and 2012, showed the inaccuracy due date in order fulfillment to customers. From the analysis of the data issues and order fulfillment, then the required material requirements planning that completed with the method of calculation of the lot-for-lot.Based on the results of testing and evaluation, it is known that the information system is built to reduce the excess due date fulfillment of customer orders. Examples of the company's customers are PT. Arga Arta Utama and PT. Nakula Sadewa, the average percentage of inaccuracy due date in order fulfillment in the year 2011 by 88 %, whereas in the year 2012 by 79 %. Presence software comparison of the percentage of inaccuracy due date fulfillment of customer orders in 2011-2012 at 0 %. So that the inaccuracy due date fulfillment of customer orders can be reduced and PT. Elang Jagad do not lose customers (stock out).Keywords : Material Requirements Planning, Lot - For- Lot, Due Date